2021
DOI: 10.3390/ani11113144
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Feeding Liquid or Dry Creep Feed on Growth Performance, Feed Disappearance, Enzyme Activity and Number of Eaters in Suckling Piglets

Abstract: The aim of this study was to investigate the effect of two dietary treatments (liquid creep feed (LCF) and dry creep feed (DCF)) offered during the suckling period on feed disappearance, number of eaters, and intestinal enzymatic development at weaning in an on-farm study with 347 piglets. Piglets were allocated to either the DCF or LCF treatment from day 10 to day 24 postpartum for 9 h a day. Red ferric oxide (1%) was added to the diet to categorize piglets into eating categories (good eaters, moderate eaters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 29 publications
0
19
1
3
Order By: Relevance
“…It is possible that the greater starch content in the COM diet (14% vs. 8% starch for COM and milk-based creep feeds, respectively) promoted jejunal mucosal maltase-specific activity before weaning. A previous study by Byrgesen et al (2021) found that, at weaning, disaccharidase activity was greater for pigs that provided a pelleted creep feed vs. a liquid feed with matched composition, despite the liquid-fed pigs consuming more feed (on dry matter-basis) for most of the preweaning feeding period. However, in the current study, differences in disaccharidase enzyme activity were not attributed to creep feed form alone.…”
Section: Discussionmentioning
confidence: 88%
“…It is possible that the greater starch content in the COM diet (14% vs. 8% starch for COM and milk-based creep feeds, respectively) promoted jejunal mucosal maltase-specific activity before weaning. A previous study by Byrgesen et al (2021) found that, at weaning, disaccharidase activity was greater for pigs that provided a pelleted creep feed vs. a liquid feed with matched composition, despite the liquid-fed pigs consuming more feed (on dry matter-basis) for most of the preweaning feeding period. However, in the current study, differences in disaccharidase enzyme activity were not attributed to creep feed form alone.…”
Section: Discussionmentioning
confidence: 88%
“…Christensen et al [ 30 ] concluded that providing supplemental nutrition such as creep feed does positively affect weaning weights, but this gain was lost over time in the nursery. On the other hand, Byrgensen et al [ 9 ] reported a tendency for dry-creep-fed piglets during lactation to have improved weight gain in the nursery. Further studies using improved creep feeder designs need to be conducted to determine whether the weight gain advantage during lactation is sustained throughout the nursery phase.…”
Section: Discussionmentioning
confidence: 99%
“…To help mitigate post-weaning stressors, creep feeding during the lactation period has been a practice utilized by the swine industry to provide nutrients to young pigs and to promote their adaptation to solid feed [ 6 , 7 , 8 ]. While there is a dearth of evidence to prove that creep feeding definitively increases weaning weight, Byrgesen et al [ 9 ] reported effects related to gruel versus dry creep feeding. Building upon this, and as technology advances, new delivery methods of creep feed are being developed, varying from behavioral stimulation to easily accessible feeder designs [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The transition from the sow’s milk to a dry and mainly plant-based feed results most often in a period of low feed intake or anorexia. In practice, suckling pigs are offered creep feed, most often dry, and less often as liquid feed, to let them become familiar to this form of feed and as a nutritional supplement to the sows milk for those piglets not being able to suckle enough [ 36 ]. Furthermore, and importantly, it is presumed that creep feed intake contributes to maturation of the gut function by stimulating the development of the gastrointestinal tract ( GI-tract ) microbiota and the activity of digestive enzymes (e.g., pancreatic enzymes and brush border enzymes) necessary to hydrolyse substrates of plant origin [ 36 , 37 , 38 ].…”
Section: Prevention Of Post-weaning Diarrhoea—mode Of Actionmentioning
confidence: 99%
“…In practice, suckling pigs are offered creep feed, most often dry, and less often as liquid feed, to let them become familiar to this form of feed and as a nutritional supplement to the sows milk for those piglets not being able to suckle enough [ 36 ]. Furthermore, and importantly, it is presumed that creep feed intake contributes to maturation of the gut function by stimulating the development of the gastrointestinal tract ( GI-tract ) microbiota and the activity of digestive enzymes (e.g., pancreatic enzymes and brush border enzymes) necessary to hydrolyse substrates of plant origin [ 36 , 37 , 38 ]. This would mean that when piglets are weaned, their digestive system is more developed and more capable of digesting and absorbing dietary nutrients than piglets not ingesting any creep feed, and that their gut microbiota can better withstand the disturbances occurring at weaning.…”
Section: Prevention Of Post-weaning Diarrhoea—mode Of Actionmentioning
confidence: 99%